2011
DOI: 10.4209/aaqr.2010.10.0086
|View full text |Cite
|
Sign up to set email alerts
|

Deep Investigation of Ultrafine Particles in Urban Air

Abstract: This work describes the results of a study which started in 2007 to investigate the ultrafine particle (UFP) pollution in the urban area of Rome. The sampling site was located in a street with high density of autovehicular traffic, where measurements have shown that carbonaceous particulate matter represented an important fraction of aerosol pollution. UFPs have been classified by means of an electrostatic classifier. Monodisperse aerosol was either counted by ultrafine water-based condensation particle counte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…The starting point of this study was to define what the relevant part of aerosol and its measure to be in Rome considering that in such urban area combustive sources represent the main contributors to submicrometric aerosol (Manigrasso et al, 2009;Fanizza et al, 2010;Avino et al, 2011). The Fig.…”
Section: Ultrafine Particle Determination In Downtown Romementioning
confidence: 99%
See 1 more Smart Citation
“…The starting point of this study was to define what the relevant part of aerosol and its measure to be in Rome considering that in such urban area combustive sources represent the main contributors to submicrometric aerosol (Manigrasso et al, 2009;Fanizza et al, 2010;Avino et al, 2011). The Fig.…”
Section: Ultrafine Particle Determination In Downtown Romementioning
confidence: 99%
“…Recently, several studies on aerosol particle number concentrations and size distribution have been published (Manigrasso et al, 2009;Fanizza et al, 2010;Avino et al, 2011; evidencing that particles in the ultrafine size range (< 100 nm) pose special problems to the lungs due to their high efficiency of deposition. Several epidemiological studies have shown associations among ambient ultrafine particles and human respiratory or cardiovascular diseases (Delfino et al, 1998;Donaldson et al, 2001;Peters et al, 2001;Von Klot et al, 2002;Brook et al, 2002;Avino and Brocco, 2004;Petraccia et al, 2005;Dominici et al, 2006;Simkhovich et al, 2008;Oliva et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…According to several studies (Dan et al, 2004;Na et al, 2004;Duan et al, 2005;Avino et al, 2011), the impact of SOC cannot be ignored. With the increase in photochemical reactions, SOC attributes high contributions to carbonaceous matter.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrafine particles are extremely small when compared with the cellular structures and have a high surface area per unit mass [29][30][31]. They form aggregates and are easily deposited as aggregates in the lungs, where it can then disaggregate.…”
Section: Resultsmentioning
confidence: 99%